2016
DOI: 10.5152/tjar.2016.20981
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Withdrawal Movement Associated with the Injection of Rocuronium in Children: Comparison of Paracetamol and Lidocaine

Abstract: Amaç: İntravenöz (i.v) roküronyum enjeksiyonu sonrası hastaların %50-80'i gibi büyük bir kısmında ağrı görülmektedir. Bu araştırma-nın amacı, genel anestezi altında ameliyat geçirecek çocuk hastalarda, i.v. roküronyum enjeksiyonuna bağlı çekme hareketini önlemede, ön-ceden uygulanan i.v. parasetamolün etkinliğini i.v. lidokain ile karşı-laştırmaktır.Yöntemler: Genel anestezi uygulanacak olan 90 hasta basit kura çek-me yöntemi ile rastgele iki gruba ayrıldı; parasetamol grubu (Grup P, n=45) ve lidokain grubu (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…during repeated injection, it has been suggested that this pain is associated with local irritant effect, thus, local anesthetic effect of lignocaine might be useful for preventing this pain. 12 As Cheong et al 5 showed that there was a decrease in pain on injection of rocuronium from 77% to 37% and 7% when lignocaine was given before rocuronium at doses of 10mg and 30mg respectively, we observed that 17 (10.6%) patients complained of mild pain, 4 (2.5%) complained of moderate pain and 1 (0.6%) patient complained of severe pain during injection of rocurounium after intravenous lignocaine.…”
Section: Prasai Et Alsupporting
confidence: 48%
See 3 more Smart Citations
“…during repeated injection, it has been suggested that this pain is associated with local irritant effect, thus, local anesthetic effect of lignocaine might be useful for preventing this pain. 12 As Cheong et al 5 showed that there was a decrease in pain on injection of rocuronium from 77% to 37% and 7% when lignocaine was given before rocuronium at doses of 10mg and 30mg respectively, we observed that 17 (10.6%) patients complained of mild pain, 4 (2.5%) complained of moderate pain and 1 (0.6%) patient complained of severe pain during injection of rocurounium after intravenous lignocaine.…”
Section: Prasai Et Alsupporting
confidence: 48%
“…Pain due to injection of anesthetic agents is perceived by polymodal nociceptors that innervate the peripheral veins. 12 The pain is more frequent and severe when the drug has non-physiological osmolality or pH values. 13 Rocuronium bromide is formulated with sodium acetate, sodium chloride, or acetic acid to produce a solution of pH 4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 90 studies were reviewed in detail, after which 29 studies were excluded for the following reasons: pediatric study [7, [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58], meta-analysis [3,59], and did not report the outcomes of interest [60][61][62][63][64][65][66]. Thus, 61 studies met the inclusion criteria and were included in this systematic review and meta-analysis (Fig.…”
Section: Study Selectionmentioning
confidence: 99%